Spatial Feasibility Evaluation of Landfill Site Policy within the National Activity Center Area of Sleman Regency’s Spatial Plan for 2021–2041 - Siham, Ahmad Fajar; Juhadi; Nugroho, Arif Rahman; Herlina, Meri (Universitas Lampung, 2025)
Sleman Regency does not have a landfill after the issuance of the Piyungan Landfill Decentralization Letter. According on Government Regulation No. 81 of 2012 Article 23, the Regency/City Government are required to provide a landfill in accordance with the RTRW and meet technical requirements. In Sleman Regional Regulation No. 13 of 2021 concerning RTRW, the PKN area is conditionally permitted to build a landfill. This research aims to evaluate the feasibility of landfill locations designated in the RTRW based on the parameters outlined in Article 23 paragraph (3) of the Government Regulation. The spatial analysis method was by overlaying and assigning scores to each parameter. Secondary data were used, obtained through agency surveys and literature studies. The results showed that the PKN area does not have an site feasible for a landfill. The research findings can be used as input in reviewing the landfill location policy.